ПРОЦЕСИ ТА ОРГАНІЗАЦІЯ КОМУТАЦІЇ ВОЛЬТОДОДАВЧИХ ТРАНСФОРМАТОРІВ - Халіков, В.А. (Інститут електродинаміки НАН України, Київ, 2011)
Transient processes appearing over core saturation on switching of the primary winding of a buck-boost transformer are considered. Visual modeling of transient processes is done with MATLAB and techniques for minimization or elimination of transients are suggested. References 5, figures 15.